Viral Sequences Recovered From Puma Tooth DNA Reconstruct Statewide Viral Phylogenies - Gagne, Roderick B.; Kraberger, Simona; McMinn, Rebekah; Trumbo, Daryl R.; Anderson, Charles R.; Logan, Ken A.; Alldredge, Mathew W.; Griffin, Karen; Vandewoude, Sue (Frontiers in Ecology and Evolution, 2021)
Monitoring pathogens in wildlife populations is imperative for effective management, and for identifying locations for pathogen spillover among wildlife, domestic species and humans. Wildlife pathogen surveillance is challenging, however, as sampling often requires the capture of a significant proportion of the population to understand host pathogen dynamics. To address this challenge, we assessed the ability to use hunter-collected teeth from puma across Colorado to recover genetic data of two feline retroviruses, Feline Foamy Virus (FFV) and Feline Immunodeficiency Virus (FIVpco) and show they can be utilized for this purpose. Comparative phylogenetic analyses of FIVpco and FFV from tooth and blood samples to previous analyses conducted with blood samples collected over a nine-year period from two distinct areas was undertaken highlighting the value of tooth derived samples. We found less FIVpco phylogeographic structuring than observed from sampling only two regions and that FFV data confirmed previous findings of endemic infection, minimal geographic structuring, and supported frequent cross-species transmission from domestic cats to pumas. Viral analysis conducted using intentionally collected blood samples required extensive financial, capture and sampling efforts. This analysis illustrates that viral genomic data can be cost effectively obtained using tooth samples incidentally-collected from hunter harvested pumas, taking advantage of samples collected for morphological age identification. This technique should be considered as an opportunistic method to provide broad geographic sampling to define viral dynamics more accurately in wildlife.